Biodegradation of linear alkylbenzene sulfonate contamination by pseudomonas aeruginosa isolates - Al-Zamili, Hussein Ali Awadh; Al-Mayaly, Ithar Kamil (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Linear alkylbenzene sulphonate (LAS), a surfactant frequently incorporated into detergent formulations, typically ends up in wastewater treatment facilities after use. The present study aims to investigate the efficacy of bacteria isolated from Iraqi wastewater in removing LAS. This strain was identified as Pseudomonas aeruginosa by genetic analysis (16S rRNA). Three LAS concentrations (25, 50, and 100 mg/l) were employed in this investigation, along with three temperatures (30, 35, and 40 oC) and pH values (5, 7, 9). The LAS anionic surfactant demonstrated optimal biodegradation by Pseudomonas aeruginosa at a temperature of 30 °C and at pH levels of 7 and 9, with removal percentages of 93.76% and 90.4%, respectively, at a concentration of 25 mg/l of LAS. The study’s findings demonstrated the possibility and importance of using aerobic biodegradation to remove LAS from actual effluents. This bacterium is useful for bioremediation because of its capacity to break down LAS.